The dynamics of remittances impact: a mixed-method approach to understand Ghana’s situation and the way forward - Asafo Agyei, Stephen (2021)
Many scholarly articles on remittance have focused on its positive or negative impact on the macro- or microeconomy. Given that trend, remittance is usually analysed without its sociological elements embedded within the migration process. Therefore, this paper employs a bird’s eye view to advance our understanding of the dynamics of remittance within the Ghanaian migration framework. By this, the paper uses a mixed-method approach to shed light on the Ghana case. First, through multiple linear regression, the paper shows that remittance inflow to Ghana is positively related to GDP per capita. Specifically, the evidence indicates that a 1% increase in remittance leads to an approximately 4% increase in the GDP per capita. Second, with the aid of household survey data from Ghana Statistical Service and Ghana’s poverty dimension, the paper shows that while the empirical finding suggests an improvement of the populace’s standard of living, the evidence on the grounds, however, conflicts with such findings. This is because remittance is primarily a private resource and is likely to reach only a few well-off homes in Ghana; hence, it does not consider an effective redistributive dimension. Third, to further elucidate why remittance reaches these few groups, the paper analyses within the Marxist political framework how legal migration to the developed countries has always been an option only for the well-off and middle-class Ghanaians who could afford the cost. With this clear establishment of the remittance dynamics in Ghana, the study proposes plausible suggestions to enhance the redistributive effect of remittance in Ghana. In particular, the study recommends a state-led online app for migrants to send money to Ghana. Notably, the state should champion this agenda because subsidising the transaction fees would make it relatively cheaper for migrants. While this would encourage migrants to use the official means, which undoubtedly is significant for the macroeconomy, the app’s returns could be used in addressing the country’s social inequality gap at the micro-level.